Modeling and stability analysis of dark energy ultra-compact objects in extended teleparallel gravity - Shahzad, M. R.; Fakhar, Liaba; Nabi, Kiran; Amjad, Zeeshan; Mubaraki, Ali M.; Yagob, Arafa A. (European physical journal plus, 2025)
Recent advances in modeling compact astrophysical objects have gained the considerable attention of certain research communities to explore the mysterious properties of the complex internal structure of stellar objects. This growing scientific attention has been strengthened by integrating dark energy as an extra relativistic source in the internal structures of these compact objects. In the present study, we investigated a new class of ultra-compact dark energy stars comprising the two matter configurations (one is ordinary matter and the other is dark energy matter) in f ( T ) gravity. The overview of the formulation of the governing field equations is presented, and the Generalized Tolman-Kuchowicz (GTK) ansatz for g tt and g rr are taken as seed solutions to obtain our proposed model for a linear model of the torsion function f ( T ) = χ + ζ T . Boundary matching conditions based on some physical consequences constrained both geometric parameters and the dark energy coupling factor when applied to a class of compact star candidates using the cosmological f ( T ) model. The solution demonstrated physical consistency through the regularity of the metrics, the adherence to the energy conditions, and the stability criteria. Notably, the model predicts maximum masses and compactness values that exceed observational limits; for instance, surface redshifts and mass-radius profiles remain in the stability and feasibility ranges. These findings imply that the proposed framework could transcend traditional observational constraints, offering predictions beyond standard astrophysical models. Crucially, the derived solutions demonstrate physical consistency, accurately replicating the equilibrium properties of a stable, ultra-dense dark energy-dominated stellar configuration. The results advance our understanding of relativistic compact objects by elucidating how modified gravitational interactions (via extended f ( T ) theories) synergize with multi-fluid systems, baryonic and dark energy components, to govern spacetime geometry and stellar dynamics.